MODEL TIKUS UNTUK NYERI NEUROPATIK PERIFER - Endang Mutiawati* (Neurona Majalah Kedokteran Neuro Sains, 2017)
THE RESEARCH ABOUT NEUROPATHIC PAIN MECHANISM IS DIRECTLY DONE TO HUMAN BUT THE STUDY PERMIT WOULD BE HARD TO GET BECAUSE OF INVASIVE FORM OF THE NERVE DESTRUCTION THIS ARTICLE WILL ELABORATE ON THE MICE MODEL OF TRAUMATIC AND NON TRAUMATIC PERIPHERAL NERVE DESTRUCTION TO INFLICT NEUROPATHIC PAIN